2011
DOI: 10.1074/jbc.m111.230904
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of G Protein-coupled Receptor Kinase 1 (GRK1) Is Regulated by Light but Independent of Phototransduction in Rod Photoreceptors

Abstract: Phosphorylation of rhodopsin by G protein-coupled receptor kinase 1 (GRK1, or rhodopsin kinase) is critical for the deactivation of the phototransduction cascade in vertebrate photoreceptors. Based on our previous studies in vitro, we predicted that Ser 21 in GRK1 would be phosphorylated by cAMP-dependent protein kinase (PKA) in vivo. Here, we report that dark-adapted, wild-type mice demonstrate significantly elevated levels of phosphorylated GRK1 compared with light-adapted animals. Based on comparatively slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…These data were originally published in the Journal of Biological Chemistry ©The American Society for Biochemistry and Molecular Biology (Ref. 25). B, Western blot analysis of retinas from 4‐ to 5‐month‐old control and GRK1‐S21A mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data were originally published in the Journal of Biological Chemistry ©The American Society for Biochemistry and Molecular Biology (Ref. 25). B, Western blot analysis of retinas from 4‐ to 5‐month‐old control and GRK1‐S21A mice.…”
Section: Resultsmentioning
confidence: 99%
“…Retinas from light exposed mice were removed from eye cups in the light using a conventional dissection microscope. Alternatively, retinas from mice maintained in the dark were removed under dim red light using an infrared dissection microscope . For homogenization, each retina was placed in 100 μL of HEPES‐Ringer buffer, followed by the addition of 150 μL of buffer consisting of 125 mM Tris‐HCl, pH 6.8, 5% SDS, 20% glycerol, and 100 mM NaF preheated to 95°C.…”
Section: Methodsmentioning
confidence: 99%
“…Using the Xenopus laevis retina as a model, it was shown that the level of the PKA-mediated phosphorylation of grk7 was diminished by light exposure (Osawa et al, 2008). Similarly, the level of GRK1 phosphorylation was higher in the dark-adapted mouse retina as compared to the light-adapted animals (Osawa et al, 2011). These data suggest that PKA phosphorylation of GRKs 1 and 7 serve as a feedback mechanism: dephosphorylation increases kinase activity upon light exposure when rapid opsin deactivation is required.…”
Section: Grk Regulationmentioning
confidence: 96%
“…These data suggest that PKA phosphorylation of GRKs 1 and 7 serve as a feedback mechanism: dephosphorylation increases kinase activity upon light exposure when rapid opsin deactivation is required. Interestingly, phototransduction does not seem to be required for the light-induced dephosphorylation of GRK1, since it is preserved in mice lacking transducin α-subunit (Osawa et al, 2011). …”
Section: Grk Regulationmentioning
confidence: 99%
“…68 While the stoichiometry of phosphorylation was not quantitatively measured, introducing phosphomimetic mutations into recombinant RGS9-1 reduced its GAP activity, suggesting that this may be a modulation mechanism for phototransduction recovery, akin to what was more recently shown for GRK1 by PKA. 69,70 While reversible protein phosphorylation is a common way of modulating enzyme activity in biochemistry, the extent to which it is used to modulate phototransduction was not understood to its full extent. This is another fertile area of discovery.…”
Section: Translocation and Regulation Of Rgs9-1mentioning
confidence: 99%